Deteksi Abnormality Dengan Menggunakan Algortima KLT Pada Citra Video CCTV - Lailia Rahmawati (FT- UNDAR, 2017)
Abnormality Detection on CCTV video images that are shown on a particular individual or a particular object where the movement is captured by a minority. The use of KLT Algorithm (Kanade-Lucas-Tomasi) as Algortima Tracing results of a video that has been done Residual Spectral process that aims to produce a global movement that allocates an interesting area. From the comparison results it is known that the number of pixels in the detection move smaller than the detection is not moving. Then the result is that, the abnormal minority is that there is an object moving on its own compared to the other objects